Ekspresywny ruch społeczny kobiet jako przykład aktywności w społeczeństwie obywatelskim - Leśniak-Moczuk, Krystyna (PRAWO i WIĘŹ, 2026)
The paper analyzes the expressive social movement of women named Krystyna as a form of grassroots civic activity within the framework of multisectoral social policy. The author places her considerations in the context of changes in the welfare state, the development of civil society, and civic (active) social policy, implemented in cooperation between the public, private, social, and informal sectors. The subject of the analysis is the nationwide Krystyna movement, operating since 1998, which has transformed from a social category linked by a common name into a new, unconventional social movement of an expressive and bond-building nature. Empirical research (surveys, interviews, participant observation) has shown that this movement promotes the integration of women, mainly senior citizens, builds social capital, and initiates grassroots social and aid activities. The Krystyn phenomenon has been interpreted in the light of classical and contemporary theories of social movements. The author argues that despite the lack of a formal program and reformist goals, the movement meets most of the criteria of a social movement, especially in terms of emotional community, informal networks of relationships, and cultural expression. The paper emphasizes the importance of the Krystyn movement as an example of the functioning of civil society, especially in the area of senior citizen policy.